PEMBIAYAAN PERDAGANGAN DALAM UPAYA PENGEMBANGAN EKSPOR UKM: ANALISIS PANEL DATA 1999-2007 - Nur Rakhman Setyoko; Firman Mutakin; I Made Dodi Narindra (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
Panel data analysis with fixed effect method is used to analyse data collected in a range of year 1999-2007. This study aims to figure out the effectiveness of trade financing implemented on Small Medium Enterprises (SMEs) Export development in Indonesia. Trade Financing contributed significantly and positively on non-oil and gas export of SMEs in Indonesia. It is clearly that accessibility improvement to trade financing will be able to open more opportunity for SMEs to improve their export performance. Regression output on panel data analysis for each sector of SMEs has concluded that working capital which has been regarded as the dominant factor for policy maker, to make policies in regard of SMEs export performance in Indonesia. Capital expansion with no improvement on human resources and market diversification will not give a strong impact to SMESs export development in Indonesia. Trade financing gives more bargain power for SMEs to importir. More bargain power will give an incentive to exporter to raise the price in international trade.